FLT3 Inhibitors in the Management of Acute Myeloid Leukemia - Zappone, E.; Defina, M.; Aprile, L.; Bartalucci, G.; Gozzetti, A.; Bocchia, M. (Anti-Cancer Agents in Medicinal Chemistry, 2017)
In recent years there has been a great improvement in molecular characterization of acute myeloid leukemia (AML) allowing the stratification of patients in different rate of risk. Patients with FLT3 mutated AML have poor prognosis because of resistance to induction chemotherapy or early relapse. Several first and second generation molecules, able to inhibit FLT3 signaling have been developed and many single agent or combination studies are ongoing. Of these, quizartinib seems to have the best clinical activity. Unfortunately, resistance to FLT3 inhibitors has been observed and many scientists are currently investigating new strategy to restore sensitivity to FLT3 inhibitors.
Keywords: FLT3